The Effect Of Structural Abnormalities Resulting From Different Dental Anomalies On Dental Adhesion: A Review (Journal of Pharmaceutical Negative Results, 2023)
Background: A number of anomalies, resulting in defective tooth structure, can occur during the process of tooth formation. Though it is impossible to stop these defects from happening but advances in the science of dental materials have led to the development of such materials and protocols which can effectively restore such defects. Although, adhesive dental procedures, in particular, might be complicated by these intrinsic or acquired anatomical abnormalities, material scientists are finding ways to improve the bond strength with these defective structures. Objective: Our goal in conducting this literature review was to discover methods that have been shown to enhance the quality of the adhesive bond between the restorative materials and aberrant tooth structures resulting from different anomalies.Methods: The systematic search was undergone in three electronic databases : PubMed, ScienceDirect and Google Scholar, using the following key words: teeth abnormalities, Dental enamel, Enamel defect, fluorosis, amelogenesis imperfecta, Acid etching, Bonding, ultrastructure. A manual search was performed based on the electronic search bilbiography.Conclusion: The findings indicate that bond strength is worse with teeth having structural defects compared to normal ones. Several methods, including deproteinization with sodium hypochlorite solution, extended etching, micro abrasion, and the application of adhesion boosters, have been proposed as potential solutions to this issue. A major difficulty in dentistry practise is presented by structural anomalies, which reduces the quality of adhesive bonding to enamel and dentine. Phosphoric acid etching and self etch systems have shown improved bonding in cases of amelogenesis imperfecta. Micro abrasion and extended etching have both been shown to be beneficial to the bonding technique in the case of fluorosis. To find methods to enhance adhesion to the teeth with structural defects, further clinical studies with extended follow-up periods are needed.